Impact of “Adverse Selection” on Managers' Project Evaluation Decisions - Harrison, Paul; Harrell, Adrian M. (Academy of Management Journal, 1993)
Agency theory can be used to explain decisions to continue a failing project. The results of a decision-making experiment provide empirical support for the proposition that when the conditions for adverse selection exist?an agent has private information and an incentive to shirk?such decisions, apparently irrational from a principal's perspective, may be rational from the agent's perspective.